Impromptu Speech Delivery among EFL Graduate Students: Challenges and Potential Strategies - Arifin, Syaadiah (Jurnal Pendidikan Progresif, 2024)
Abstract: Impropmtu Speech Delivery Among EFL Graduate Students: Challenges and Potential Strategies. Objectives: This study explores the challenges confronted by EFL (English as a Foreign Language) graduate students in delivering impromptu speeches, especially in formal settings. Method: The research included twelve graduate students in their first semester of the 2013/2014 academic year, majoring in English Education at a private university in Jakarta. It employed a mixed-methods approach and was descriptive in nature. Data collection tools consisted of questionnaires, interviews, reflective journals, and observations. Quantitative data were obtained from questionnaires, while qualitative data came from interviews, observations, and reflective journals completed by the students as an assignment. Findings: The study identified high anxiety and difficulties in organizing and articulating thoughts spontaneously as the primary challenges. It also noted that sufficient practice and the teacher support were effective in reducing students' anxiety and improving their speaking abilities. Conclusion The research revealed that anxiety, stemming from insufficient preparation due to time constrain and unfamiliar topics, adversely affected the speech quality. In response, the teacher focused on enhancing emotional awareness and minimizing anxiety levels. The study underscored the significance of teacher-led initiatives in creating supportive learning environment. Keywords: impromptu speaking, graduate students, challenges, strategies.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202430